Perancangan Aplikasi Pendataan Pelanggan pada Perusahaan PT. Indomobil Trada Nasional - Ambar Tri Hapsari; Aswin Fitriansyah (Jurnal Informatika Universitas Pamulang, 2020)
PT Indomobil Sukses International Tbk. (The Company) is the main company of the automotive group of companies. This company has many well-known automotive subsidiaries in Indonesia. This automotive company attaches great importance to products to meet customer needs and satisfaction. Guaranteed quality standards are the company's principle by supporting after-sales service in the 3S network (Sales, Service, and Spare parts) that already exist throughout Indonesia. The target of this company's business process must optimize customer data so that the company's target is not difficult to achieve in order to compete with other companies that have used computerized systems. Based on the description, the theme of research on designing customer data collection applications at PT. Indomobil Trada Nasional.